Pengaruh Kemudahan Transaksi Cashless terhadap Pengeluaran Generasi Z - Anggita Maghfiroh; Fadya Dwi Aglika; Ghaitsa Azahra; Nelvi Santika; Shilva Olivia Stiadi; Palupi Permata Rahmi; Asep Wahyu Mulyadi (CV. ITTC INDONESIA, 2026)
The rapid development of digital technology has transformed payment systems from cash-based transactions to cashless transactions. Various digital payment services, such as Quick Response Code Indonesian Standard (QRIS), e-wallets, mobile banking, and debit cards, offer convenience, speed, and efficiency in conducting financial transactions. As a generation with high technological adaptability, Generation Z is the primary user of digital payment systems, making cashless transactions likely to influence their spending patterns. This study aims to analyze the effect of cashless transaction convenience on the spending patterns of Generation Z. A quantitative approach with a survey method was employed in this study. The population consisted of Generation Z individuals who had used cashless payment methods. The sample consisted of 91 respondents who met the research criteria and were selected using a purposive sampling technique. Data were collected through a Google Forms questionnaire and analyzed using validity testing, reliability testing, normality testing, simple linear regression, ANOVA Test (F-test), t-test, and the coefficient of determination (R²) with Jamovi software. The findings indicate that the convenience of cashless transactions does not have a statistically significant effect on the spending patterns of Generation Z. This is evidenced by a significance value of 0.124 (p > 0.05) and a coefficient of determination (R²) of 0.0269, indicating that cashless transaction convenience explains only 2.69% of the variation in spending patterns. Therefore, cashless transaction convenience is not the primary factor influencing the spending behavior of Generation Z. Other factors, such as financial literacy, income level, lifestyle, and self-control, are likely to have a greater influence. These findings are expected to provide useful insights for digital payment service providers and future researchers.